56 days - Howard, Catherine Ryan (Blackstone Publishing, 2021)
No one knew they'd moved in together. Now one of them is dead. Could this be the perfect murder? 56 DAYS AGO Ciara and Oliver meet in a supermarket queue in Dublin the same week Covid-19 reaches Irish shores. 35 DAYS AGO When lockdown threatens to keep them apart, Oliver suggests that Ciara move in with him. She sees a unique opportunity for a new relationship to flourish without the pressure of scrutiny of family and friends. He sees it as an opportunity to hide who - and what - he really is. TODAY Detectives arrive at Oliver's apartment to discover a decomposing body inside. Will they be able to determine what really happened, or has lockdown provided someone with the opportunity to commit the perfect crime?